El bienestar de la población y el uso de tecnología de la información y comunicaciones en Loreto, periodo 2014 - 2018 - Arrué Flores, Jorge Luis (2021)
Information and communication technologies (ICTs) play a fundamental role in the advancement of society, but not all have the same weighting. The objective of this thesis was to determine the relationship between the well- being of the population and the use of information and communications technology in Loreto, in the period 2014 - 2018. For this purpose, this quantitative research was carried out, level Correlational and Non-Experimental design The research concludes that the well-being of the population has no relationship whatsoever with information and communication technologies in the department of Loreto, in the period of the five years studied, having obtained a Correlation Coefficient that was r = 0.727543569, value too far from +1. Likewise, the Determination Coefficient was R2 = 0.529319644; very far from 1; which shows the non-existence of statistical significance between both variables. In the same way, the analysis of the information media shows that open-signal television is the most used by households in Loreto, being demanded by 65.50%. On the other hand, 70.46% of households use the cell phone as a means of communication, being the most required by the accessibility to the price of the existing equipment and plans. The average real monthly per capita expenditure had a variable behavior during all the investigated years, the highest being in 2018 with S /. 651.00.